Murky morality : lack of evidence for the moral foundations hypothesis in an online dataset : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Bidwell, Alexander Stewart Duncan (Massey University, 2020)
Moral Foundations Theory uses a taxonomy of five moral foundations to categorise individuals. The Moral Foundations Hypothesis (MFH) (Graham, Haidt, & Nosek, 2009) predicts that individuals identifying as politically liberal will be more concerned with the individualising foundations of Harm/Care and Fairness/Reciprocity than the binding foundations of Ingroup/Loyalty, Authority/Subversion and Purity/Sanctity. It also predicts that those identifying as politically conservative will be evenly concerned with all five foundations, while simultaneously showing more concern for the three binding foundations than liberals. This relationship can be assessed, as is the case in the current study, using the Moral Foundations Questionnaire, a descriptive measure of morality (Graham et al., 2009). This study sought to establish whether the prediction made by the MFH would be supported using a large sample (N = 1261) gathered through the online Facebook research application myPersonality.org. Several different statistical strategies were used to test the hypothesis: pre-registered structural equation modelling (including confirmatory factor analysis); casebased analysis; exploratory correlational analysis, and exploratory factor analysis. Results of the analysis did not support the predictions of the MFH. The confirmatory models did not reach acceptable levels of fit, based on the fit index thresholds set in the study preregistration. However, the regression estimates from the Structural Equation Model were in the predicted directions. Additionally, the exploratory case-based analysis revealed tentative support for the MFH predictions.
Keywords: 520599 Social and personality psychology not elsewhere classified